A framework for identifying and analysing industry 4.0 scenarios. (October 2022) - de Paula Ferreira, William; Armellini, Fabiano; de Santa-Eulalia, Luis Antonio; Thomasset-Laperrière, Vincent
Abstract: Industry 4.0 is a central strategy to strengthen the competitiveness of the manufacturing sector over the next years. Nevertheless, there is a lack of common understanding of Industry 4.0 and tools to help companies' transformation to Industry 4.0, especially for small and medium-sized enterprises (SMEs). To address these research gaps, this study proposes a framework to characterise and evaluate Industry 4.0 scenarios to aid companies' transition towards Industry 4.0. For this, a design science (multi-methodological) approach is adopted, including an Industry 4.0 use case survey, modelling and simulation and two proof-of-concept cases developed in collaboration with a Canadian college centre for technology transfer. The results indicate that the proposed framework can help companies identify Industry 4.0 scenarios more intuitively to assist project conception, portfolio selection and planning during Industry 4.0 roadmap development. Finally, the results of this study suggest that Industry 4.0 can be implemented incrementally while companies increase their digital capabilities and maturity. Highlights: Introduce a new approach to support the implementation of Industry 4.0. Identifies 684 use cases of Industry 4.0. Presents two cases developed with a Canadian college centre for technology transfer.